Unhomely: Redefining the British Decorative Arts - Iris Moon (Yale University, 2021)
This issue proposes a double move to readers. First, it foregrounds the fact that slavery, colonialism, and empire were integral historical components in the production, consumption, and reception of the British decorative arts. Second, it suggests that readers unhinge the “heritage” aspect that has long been associated with the British decorative arts, proposing instead a move of defamiliarization and making strange the routines of domesticity that seem self-evident and simply “the way things always have been”.